2012
DOI: 10.1073/pnas.1116334109
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and rotor self-assembly in active particle suspensions

Abstract: Adding a nonadsorbing polymer to passive colloids induces an attraction between the particles via the "depletion" mechanism. High enough polymer concentrations lead to phase separation. We combine experiments, theory, and simulations to demonstrate that using active colloids (such as motile bacteria) dramatically changes the physics of such mixtures. First, significantly stronger interparticle attraction is needed to cause phase separation. Secondly, the finite size aggregates formed at lower interparticle att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
300
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(312 citation statements)
references
References 23 publications
12
300
0
Order By: Relevance
“…(30-34). Recently, a number of studies revealed that crowding effects by extracellular substances can operate in bacterial cultures as well (35)(36)(37)(38)(39)(40). However, these earlier works study the role of depletion attraction operating in an equilibrium mixture of fixed bacterial cells and polymer concentration.…”
mentioning
confidence: 91%
“…(30-34). Recently, a number of studies revealed that crowding effects by extracellular substances can operate in bacterial cultures as well (35)(36)(37)(38)(39)(40). However, these earlier works study the role of depletion attraction operating in an equilibrium mixture of fixed bacterial cells and polymer concentration.…”
mentioning
confidence: 91%
“…4D. This scheme is significantly simpler than the previous examples because the active colloids simply rotate about the micropillars, and there are many ways to get colloids to actively rotate (7,(25)(26)(27)(28)(29). Despite the simplicity of the motion of the individual active particles, the combination is sufficient to create a braid, further demonstrating the robustness of active particles as an assembly machine.…”
Section: Physicsmentioning
confidence: 99%
“…This has led to the growth of the field of active matter, which aims to design, control, and understand self-propelled particles (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These active particles provide significant yet untapped potential: by combining this mechanism for energy input with controllable interactions, it becomes possible to imagine the creation of colloidal-scale machines that can do work and perform tasks.…”
mentioning
confidence: 99%
“…There has been a considerable amount of work on swimmers that can propel themselves by cyclically changing their shapes (14). Interactions between such swimmers and their collective flows have been analyzed (15)(16)(17)(18)(19)(20)(21). Also, interactions between active hydrodynamic dipoles have been investigated theoretically (22,23) and experimentally (24,25).…”
mentioning
confidence: 99%